Effect of Alkyl Chain Branching Point on 3D Crystallinity in High N‐Type Mobility Indolonaphthyridine Polymers. (28th September 2017) - Fallon, Kealan J.; Santala, Annikki; Wijeyasinghe, Nilushi; Manley, Eric F.; Goodeal, Niall; Leventis, Anastasia; Freeman, David M. E.; Al‐Hashimi, Mohammed; Chen, Lin X.; Marks, Tobin J.; Anthopoulos, Thomas D.; Bronstein, Hugo
Abstract: Herein, this study investigates the impact of branching‐point‐extended alkyl chains on the charge transport properties of three ultrahigh n‐type mobility conjugated polymers. Using grazing incidence wide‐angle X‐ray scattering, analysis of the crystallinity of the series shows that while π–π interactions are increased for all three polymers as expected, the impact of the side‐chain engineering on polymer backbone crystallinity is unique to each polymer and correlates to the observed changes in charge transport. With the three polymers exhibiting n‐type mobilities between 0.63 and 1.04 cm 2 V −1 s −1, these results ratify that the indolonaphthyridine building block has an unprecedented intrinsic ability to furnish high‐performance n‐type organic semiconductors. Abstract : The effect of alkyl side‐chain branching position on charge transport in organic semiconductors exhibiting high crystallinity is discussed herein. This study confirms that the indolonapthryidine building block has an intrinsic ability to facilitate ultrahigh n‐type mobility in organic field‐effect transistors, of which examples remain lacking, with recorded μe = 0.63–1.04 cm 2 V −1 s −1 .